2021
DOI: 10.7717/peerj.11316
|View full text |Cite
|
Sign up to set email alerts
|

High glucose treatment promotes extracellular matrix proteome remodeling in Müller glial cells

Abstract: Background The underlying pathomechanisms in diabetic retinopathy (DR) remain incompletely understood. The aim of this study was to add to the current knowledge about the particular role of retinal Müller glial cells (RMG) in the initial processes of DR. Methods Applying a quantitative proteomic workflow, we investigated changes of primary porcine RMG under short term high glucose treatment as well as glycolysis inhibition treatment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 69 publications
2
2
0
Order By: Relevance
“…Our data confirm that Müller cells are crucially involved in immunological processes in the retina as well, as they possess an antigen processing and presenting machinery and secrete proinflammatory cytokines (Karlstetter et al, 2015). We have previously shown that the cultivation of primary porcine Müller cells under hyperglycemic conditions resulted in higher expression levels of MHC class II molecules, pointing towards an immunologically activated state of Müller cells in DR (Sagmeister et al, 2021).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Our data confirm that Müller cells are crucially involved in immunological processes in the retina as well, as they possess an antigen processing and presenting machinery and secrete proinflammatory cytokines (Karlstetter et al, 2015). We have previously shown that the cultivation of primary porcine Müller cells under hyperglycemic conditions resulted in higher expression levels of MHC class II molecules, pointing towards an immunologically activated state of Müller cells in DR (Sagmeister et al, 2021).…”
Section: Discussionsupporting
confidence: 80%
“…No experimental animals were involved in this study. Within 2 h after enucleation, eyes were processed under a laminar flow hood under sterile conditions as previously described (Lorenz et al, 2021b;Sagmeister et al, 2021). In short, periocular tissue was removed and the eyeballs were rinsed in 80% ethanol followed by washing with cold PBS.…”
Section: Cell Preparation and Culturementioning
confidence: 99%
“…Our data confirm that Müller cells are crucially involved in immunological processes in the retina as well, as they possess an antigen processing and presenting machinery and secrete proinflammatory cytokines (Karlstetter et al, 2015). We have previously shown that the cultivation of primary porcine Müller cells under hyperglycemic conditions resulted in higher expression levels of MHC class II molecules, pointing towards an immunologically activated state of Müller cells in DR (Sagmeister et al, 2021).…”
Section: Discussionsupporting
confidence: 80%
“…No experimental animals were involved in this study. Within 2 h after enucleation, eyes were processed under a laminar flow hood under sterile conditions as previously described (Lorenz et al, 2021b;Sagmeister et al, 2021). In short, periocular tissue was removed and the eyeballs were rinsed in 80% ethanol followed by washing with cold PBS.…”
Section: Cell Preparation and Culturementioning
confidence: 99%